A spontaneous paraganglioma–pheochromocytoma syndrome - Toutounchi, Sadegh (Polish Urological Association, 2013)
We present a case of a 40–year old woman diagnosed with a four–place spontaneous paraganglioma–pheochromocytoma syndrome, which was treated surgically. The presence of the succinate dehydrogenase complex subunit D (SDHD) mutation that causes the pheochromocytoma was confirmed but no mutations in the family members were found. After the excision of the paragangliomas located in the areas of the division of carotid arteries, and mediastinum, as well as a tumor on the left site of the celiac trunk, the patient remains asymptomatic and is regularly followed–up.